Lactobacillus reuteri DSM 17938 shortens acute infectious diarrhea in a pediatric outpatient setting - (:unkn) unknown (SOC BRASIL PEDIATRIA, 2015)
Objective: Two randomized controlled clinical trials have shown that Lactobacillus (L) reuteri DSM 17938 reduces the duration of diarrhea in children hospitalized due to acute infectious diarrhea. This was the first trial evaluating the efficacy of L. reuteri DSM 17938 in outpatient children with acute infectious diarrhea. Methods: This was a multicenter, randomized, single-blinded, case control clinical trial in children with acute watery diarrhea. A total of 64 children who presented at outpatient clinics were enrolled. The probiotic group received 1 x 10(8) CFU L. reuteri DSM 17938 for five days in addition to oral rehydration solution (ORS) and the second group was treated with ORS only. The primary endpoint was the duration of diarrhea (in hours). The secondary endpoint was the number of children with diarrhea at each day of the five days of intervention. Adverse events were also recorded. Results: The mean duration of diarrhea was significantly reduced in the L. reuteri group compared to the control group (approximately 15h, 60.4 +/- 24.5 h [95% CI: 51.0-69.7h] vs. 74.3 +/- 15.3 h [95% CI: 68.7-79.9h], p < 0.05). The percentage of children with diarrhea was lower in the L. reuteri group (13/29; 44.8%) after 48 h than the control group (27/31; 87%; RR: 0.51; 95% CI: 0.34-0.79, p< 0.01). From the 72nd hour of intervention onwards, there was no difference between the two groups in the percentage of children with diarrhea. No adverse effects related to L. reuteri were noted. Conclusion: L. reuteri DSM 17938 is effective, safe, and well-tolerated in outpatient children with acute infectious diarrhea. (C) 2015 Sociedade Brasileira de Pediatria. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Lactobacillus reuteri DSM 17938; Diarrhea; Children; Probiotic; Ambulatory care; ACUTE GASTROENTERITIS; CHILDREN; MANAGEMENT; PROBIOTICS